Considerazioni sulla concezione cosmotecnica di Hui - Ratto Vaquer, Lorenzo Maria (Mechane, 2022)
his text analyses the concept of cosmotechnics starting from the reflections of Yuk Hui, contained in the essay The Question Concerning Technology in China: An Essay in Cosmotechnic, recently translated in Italy by Nero Editions. Going over the critical points, it wants to demonstrate how the relationship between technique and metaphysics outlined in Hui’s essay is not only valid for Chinese culture, but it is also an opportunity for reflection for Western philosophy. On the one hand, the considerations of the Hong Kong philosopher arise mainly from the idea that it is necessary to develop a different approach to this question in the Chinese context, since in China it is not present the concept of technology as understood in Western philosophy, in particular in the meaning that this concept took from Heidegger’s reflections; on the other hand, these reflections highlight some intrinsic criticalities of the Western philosophical approach towards technology. According to Hui, the concept of cosmotechnics would be useful in overcoming these criticalities since it places on the same level what Western philosophy has placed on distinct levels, namely ontology, morality, and technology. This does not simply mean bringing together these three planes, without considering their differences, but conceiving them in a relational way, that is, following the Taoist and Confucian cosmological conception, where natural order and moral order constantly dialogue. The validity of these considerations and any further developments of this approach will be analysed, with particular regard to the numerous passages in which the author emphasizes the differences between his conception of the relationship between technology and metaphysics and Heidegger’s one.